Development of functional cookies form wheat-pumpkin seed based composite flour - Weldeyohanis Gebremariam, Feriehiwote; Tadesse Melaku, Eneyew; Sundramurthy, Venkatesa Prabhu; Woldemichael Woldemariam, Henock (Heliyon, 2024)
To develop high quality cookies, even seemingly smallest changes depended on factors that can affect taste, texture, and nutritional value. In this light, this study aimed to investigate the upshot of refined wheat flour and pumpkin seed flour on properties of cookies such as antioxidant activity, thermal and oxidative stability. In view of the foregoing, the roasted pumpkin seeds of particle size below 500 μm were blended with wheat flour at different ratios (BR) to bake at selected pre-determined temperatures (T) and time durations (TD). The synergetic effect of aforesaid parameters on cookie development, BR, T, and TD was studied by varying the parameters between the range 6–15 %, 180–200 °C and from 8 to 12 min, respectively, for the baking process of cookies. Further, the process was modelled and scrutinized using numerical optimization to achieve a highly acceptable product. On that account, it was deduced that the optimal condition for BR, T, and TD were 12.87 %, 186 °C and 9.5 min, respectively, that could pave to beget the excellent quality cookies with overall acceptance score of 8, protein content 14.28 %, fat 17.85 %, ash 2.23 %, moisture 2.46 %, fiber 2.38 % and total color difference 12.01. The optimized cookies (OCs) were found to have higher protein (11.49–14.28 %), fiber (0.93–2.41 %), ash (2.19–1.77 %), total antioxidant activity (38.7158–43.1860 %), oxidative stability (28.61–51.24 h), Zn (1.42–2.63 mg/100g), and Fe (2.12–3.20 mg/100g) content as compared to the control. Laconically, the study results provided the optimized processing condition for developing high quality cookies with respect to improved nutritional value and comparable overall acceptability.